Pesticides : - Ragsdale, Nancy N (American Chemical Society, 1999)
This book examines the risks and benefits of pesticides and highlights the key points of U.S. pesticide requirements, avenues to reduce risks, factors that weigh in the determination of benefits of pesticides, and global considerations.